2018
DOI: 10.1103/physrevlett.121.117601
|View full text |Cite
|
Sign up to set email alerts
|

Direct Magnetization-Polarization Coupling in BaCuF4

Abstract: Herewith, first-principles calculations based on density functional theory are used to describe the ideal magnetization reversal through polarization switching in BaCuF_{4} which, according to our results, could be accomplished close to room temperature. We also show that this ideal coupling is driven by a single soft mode that combines both polarization, and octahedral rotation. The later being directly coupled to the weak ferromagnetism of BaCuF_{4}. This, added to its strong Jahn-Teller distortion and its o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 56 publications
5
12
0
Order By: Relevance
“…It is interesting to remark that these results were obtained considering Heisenberg interactions and single-ion anisotropy terms only while similar results were obtained by Ederer et al [23] for the BaNiF 4 compound and A. C. Garcia-Castro et al [20] for the BaCuF 4 system using an alternative description with effective single ion anisotropy contributions and a Dzyaloshinskii-Moriya interaction.…”
Section: Magnetic Ordersupporting
confidence: 82%
See 2 more Smart Citations
“…It is interesting to remark that these results were obtained considering Heisenberg interactions and single-ion anisotropy terms only while similar results were obtained by Ederer et al [23] for the BaNiF 4 compound and A. C. Garcia-Castro et al [20] for the BaCuF 4 system using an alternative description with effective single ion anisotropy contributions and a Dzyaloshinskii-Moriya interaction.…”
Section: Magnetic Ordersupporting
confidence: 82%
“…This canting produces an additional weak antiferromagnetism in the (a, c) plane. More recently, A. C. Garcia-Castro et al [20] showed that the same canting of the magnetic moments, due to an effective DM interaction coupled to the polar character of the system, also takes place in the BaCuF 4 compound. It results in the possibility to reverse, in both systems, this canting order parameter using an electric field [24].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The final class of type-I multiferroics, which was discovered long ago but recently addressed once more, is fluorides, BaMF 4 (M = Mn, Ni, Co, Fe, Cu) [ 39–41 ]. The ferroelectricity is believed to originate from the collective rotation of MF 6 octahedra, and transition metals provide magnetism.…”
Section: Type-i Multiferroicsmentioning
confidence: 99%
“…reported that a solution to this problem is to entangle octahedra rotations and ferroelectric polarization in a single soft phonon mode 161 . They reported such a possibility in BaCuF4, which is polar directly below its melting temperature (1000 K) and is a canted antiferromagnetic below its Néel temperature (TN=275 K) with weak ferromagnetism, thus making BaCuF4 multiferroic.…”
Section: Embedding Ferroelectricity and Octahedra Rotation In A Single Phonon Modementioning
confidence: 99%